(untitled) (Hekima Review, 2013)
This essay builds on an observation. One remarkable aspect of the Eu-charistic fresco of the Hekima College chapel is the outline of a city, the city of Nai-robi from all indications, represented at the base of the central panel of the painting. This aspect of the painting confronts the keen viewer. Through the realism employed by the artist, Fr. Engelbert Mveng, SJ, the viewer is led to identification of and withthe work. Not only is one able to recognize a definite place this work relates to but more intriguingly one identifies oneself with the work, viewing it within the chapel of Hekima College. In a sense, one is thrust into the painting.